ONLINE INSTRUCTIONAL STRATEGIES FOR ENGLISH LANGUAGE LEARNERS DURING THE COVID-19 PANDEMIC: PAKISTANI PERSPECTIVE OF UNIVERSITY ACADEMICS - Muhammad Asad Habib; Aneeqa Zafar; Zafar Iqbal Bhatti (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
This type of study of research aims to investigate various strategies that are being adopted by language learners as students in innovative ways in the time period of pandemic Covid-19. This conduct investigates the learners of higher-level education. The students that participated in this study were 102 that includes 16 or 15.69% male students and 86 or 84.32% female students. The prime conduct of the students is from of English Language and Literature Program Faculty of Languages and Literature, University of Management and Technology, Lahore. The basic tool for the research was questionnaire whose objective is to research and find innovative language learning strategies in various manners during the time of pandemic by measuring it through the 20-item Likert-scale. The instrument as the questionnaire and the report were being written in local perspective and the pupils were interrogated to evaluate and grade their level of cognition and perception on the strategies being asked. The study says, that students had enhanced and improved their active listening skills by using the online platforms. Online platforms helped them to learn by listening such as the online lectures. It also says that every type and level of the students are being invited by the lecturers in online learning to comment on. Improvement in the vocabulary and fluency through various audio-visual platforms like films etc. This helps the students to build confidence through active participation. Even the other skills are also being developed other than listening such as reading. The students try to find support materials by reading and also reading of the teaching materials. In this manner, they are motivated to reading skills.